METODE PEMROGRAMAN LINIER DENG-FENG LI UNTUK MENYELESAIKAN MASALAH TEORI PERMAINAN DENGAN MATRIKS PEMBAYARAN BILANGAN TRIANGULAR FUZZY - Armydia Triyuliyanti (MATEMATIKA FSM, UNDIP, 2017)
ABSTRACT. Game theory is a branch of mathematics that used to make some decisions in the competitive situations with goal to have an optimal profit. Game theory of matrix payoffs with parameters triangular fuzzy number called matrix games with payoffs of triangular fuzzy numbers. Resolving game theory problem with triangular fuzzy numbers must be converted before hand in the from of matrix game with payoffs of triangular fuzzy numbers. In this paper, we explain that this two person zero sum game mixed strategy linier programming method and Deng-Feng Li’s model in that matrix game. We also explain about how to applicating two person zero sum model to solve the marketing problem.Keywords: Game Theory, Zero Sum Game, Fuzzy Number, Linier Programming Method, Deng-Feng Li’s model